Prototyping and the new spirit of policy-making. Issue 3 (3rd July 2017) - Kimbell, Lucy; Bailey, Jocelyn
Abstract: This conceptual paper discusses the use of Co-Design approaches in the public realm by examining the emergence of a design practice, prototyping, in public policy-making. We argue that changes in approaches to management and organisation over recent decades have led towards greater flexibility, provisionality and anticipation in responding to public issues. These developments have co-emerged with growing interest in prototyping. Synthesising literatures in design, management and computing, and informed by our participant observation of teams inside government, we propose the defining characteristics of prototyping in policy-making and review the implications of using this approach. We suggest that such activities engender a 'new spirit' of policy-making. However, this development is accompanied by the further encroachment of market logics into government, with the danger of absorbing critiques of capitalism and resulting in reinforced power structures.